2006
DOI: 10.1159/000096372
|View full text |Cite
|
Sign up to set email alerts
|

Projections to the Preoptic Area from the Paraventricular Nucleus, Arcuate Nucleus and the Bed Nucleus of the Stria Terminalis Are Unlikely to Be Involved in Stress-Induced Suppression of GnRH Secretion in Sheep

Abstract: Stress compromises reproductive function and the major physiological system activated during stress is the hypothalamo-pituitary-adrenal axis. Corticotrophin-releasing hormone and arginine vasopressin (AVP), which are produced in neurones of the paraventricular nucleus (PVN), drive the hypothalamo-pituitary-adrenal axis and are also implicated in the suppression of the reproductive axis. We used retrograde tracing and Fos labelling to map the projections from the PVN to the preoptic area (POA) where most gonad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
19
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 116 publications
(78 reference statements)
3
19
0
Order By: Relevance
“…One study (4), which included gonadectomized and gonad intact sheep (luteal phase females), found that females had a greater cortisol response than males, and in three other studies (13)(14)(15) in gonadectomized sheep, we found no sex differences. The reasons for these differences between studies are not clear.…”
mentioning
confidence: 48%
See 2 more Smart Citations
“…One study (4), which included gonadectomized and gonad intact sheep (luteal phase females), found that females had a greater cortisol response than males, and in three other studies (13)(14)(15) in gonadectomized sheep, we found no sex differences. The reasons for these differences between studies are not clear.…”
mentioning
confidence: 48%
“…Isolation/restraint stress is a wellcharacterized stressor that we have used often in our laboratory (4,7,8,(13)(14)(15)20). Isolation/restraint stress involves moving the animal from a pen adjacent to a familiar sheep to an unfamiliar pen that has no sheep housed in adjacent pens, securing the animal to the side of the pen with a harness, and enclosing the pen using opaque materials (13).…”
Section: Experiments 2: Plasma Concentrations Of Cortisol In Response mentioning
confidence: 99%
See 1 more Smart Citation
“…The regional discrepancy in immunoactive GnRH may be largely explained by the fact that the Arc that is the key area of the steroid hormone feedback regulation on GnRH (Yeo & Herbison 2014). In immunized male rats, the fairly low level of testosterone negatively feedback regulates the production of GnRH neurons in the Arc instead of the Pa and MPN, which contain many GnRH cell bodies to regulate other hypophysiotropic hormone releasing hormones besides GnRH (Van Vugt et al 1997, Rivalland et al 2006. Likewise, the release of GnRH was significantly suppressed via reduction in the conveyance of GnRH to its nerve terminals in the ME of immunized rats (Glanowska & Moenter 2015).…”
Section: Figurementioning
confidence: 99%
“…in pigs, Kanitz et al 2003, Loijens et al 2002, Piekarzewska et al 1999, Piekarzewska et al 2000, Zanella et al 1996 have demonstrated the involvement of neuropeptides such as CRF and enkephalins in different brain areas including the hypothalamus, brainstem and cortices. While neuroanatomical methods have been used to describe the immunoreactive content of brain areas (in sheep: Tillet 1995; in pigs: Kineman et al 1989, Leshin et al 1996, Niblock et al 2005, Rowniak et al 2008; in large mammals: Tillet & Kitahama, 1998), and neuronaltracing methods have been used to describe the interconnections between some of these brain areas (sheep: Qi et al 2008, Rivalland et al 2006, Tillet et al 1993pigs: Chaillou et al 2009), no dynamic functional information is available about the functional interactions among these different factors. The use of MRI techniques could be an interesting way of gaining a better understanding of the neuronal circuits of animal emotion and other functions.…”
Section: Emotional Reactionmentioning
confidence: 99%